Export Stimuli, Export Stages and Internationalization Pathways: The Case of Indonesian SMEs - Mohamad Dian Revindo; Christopher Gan (Economics and Finance in Indonesia, 2016)
Small and Medium-sized Enterprises (SMEs) in developing countries are still constrained to seize the opportunity of trade liberalization as compared to their large counterparts. It has been argued that effective efforts to foster SME export require clear understanding of the factors that stimulate them to export. This study investigates the export stimuli of 385 Indonesian SMEs at different export stages (pre-exporting and exporting) and different internationalization pathways (domestically established exporter and born-global SMEs). Three types of export stimuli are consistently identified as the most important in all sub-samples: the presence of foreign buyers, the confidence in the products and the aspiration to find alternative markets. By contrast, two types of export stimuli are consistently found as the least important in all sub-samples: government support and Indonesian diaspora communities. The academic and policy implications of the findings are discussed. AbstrakKontribusi Usaha Kecil dan Menengah (UKM) terhadap ekspor di negara berkembang masih sangat terbatas. Hasil studi sebelumnya menunjukkan bahwa upaya meningkatkan ekspor UKM memerlukan pemahaman akan faktor-faktor yang mendorong ekspor (pemicu ekspor). Studi ini meneliti pemicu ekspor pada 385 UKM di Indonesia, meliputi UKM pada tahapan pra-ekspor dan eksportir serta meliputi UKM dengan jalur internasionalisasi yang berbeda. Hasil studi ini menunjukkan bahwa terdapat tiga jenis pemicu utama ekspor: kontak dari calon pembeli luar negeri, rasa percaya diri atas produk dan keinginan untuk memperluas pasar. Sebaliknya, dukungan pemerintah dan komunitas diaspora Indonesia belum menjadi pemicu utama ekspor. Temuan ini memiliki implikasi bagi diskursus akademis dan pengambil kebijakan di bidang pengembangan UKM.Kata kunci: Pemicu Ekspor; Usaha Kecil dan Menengah (UKM); Tahapan Ekspor; Jalur Internasionalisasi; Perusahaan Born-Global; IndonesiaJEL classifications: F23; L25; M13; M16; O17